A Comprehensive Online Classroom Of Interactive Multimedia Course for Lecture Sessions, Lab Tutorials and Project Exhibition Using Ufuture as MOOC platform / Zazaleena Zakariah ... [et al.] - Zakariah, Zazaleena; Noradzan, Haslinda; Ismail, Juhaida; Abdul Rahman, Rozeleenda; Abdul Razak, Nawal (2021)
Massive Open Online Courses (MOOC) is an emerging learning approach where learners can experience the teaching and learning processes via online platform. Universiti Teknologi MARA (UiTM) launch its own in-house developed platform named as UFUTURE that tailored to UiTM needs in September 2019. UFUTURE integrates full-time and part time learners and MOOCs users from all UiTM campuses. With the main objective to enhance the quality of learning and teaching, UFUTURE has improved user accessibility and time flexibility to engage learners in the learning process. Responding to the boundless potential of UFUTURE, the development of MOOC for Interactive Multimedia course (CSC253) has been initiated. This project objectives are to provide online learning platform by utilizing MOOC features provided in UFUTURE to cater wide diversities of learners' preferences, to embed traditional face-to-face teaching in the online learning environment and to give opportunity for research and development in online education. Through this project, a comprehensive online classroom that comprises components for lecture sessions and lab tutorials are developed. Each component incorporated with clear instructions, comprehensive notes, inclusive teaching videos, helpful additional materials, fascinating activities, adequate self-assessment questions and a well- designed feedback survey. All of these components are vital in the process of achieving the project objectives of becoming a comprehensive online classroom for the Interactive Multimedia Course. Besides that, this project takes extend measures by using UFUTURE as a project exhibition platform that becomes as students' project showcase which includes posters, montages and video projects. This paper also presents promising positive findings obtained from feedback surveys which indicate the effectiveness of this online classroom in delivering its objectives.